Chemistry and Clinical Relevance of Carbohydrate Degradation in Drugs - Pischetsrieder, Monika; Gensberger-Reigl, Sabrina; Atzenbeck, Lisa; Weigel, Ingrid (Drug Discovery Today, 2016)
Carbohydrate degradation products are formed during heat sterilization in drugs containing (poly-)glucose as osmotic agents. Given this situation, peritoneal dialysis fluids (PDFs) and infusion fluids are of particular clinical relevance, because these drugs deliver process contaminants either over a longer period or directly into the circulation of patients who are critically ill. For the development of suitable mitigation strategies, it is important to understand the reaction mechanisms of carbohydrate degradation during sterilization and how the resulting products interact with physiological targets at the molecular level. Furthermore, reliable, comprehensive, and highly sensitive quantification methods are required for product control and toxicological evaluation.